Evaluating students’ bread preferences in UiTM Perlis: an application of the fuzzy analytical hierarchy process - Abd Aziz, Khairu Azlan; Wan Daud, Wan Suhana; Mohd Idris, Mohd Fazril Izhar; Kamal Azman, Nur Aqilah; Saian, Rizauddin (UiTM Cawangan Perlis, 2025)
Nowadays, the food industry has expanded significantly, attracting many investors to invest in this business. Among these, the popularity of bread has been increasing, and many brands are available in the market. Bread has become a popular alternative food, especially among students, as it is convenient to store and carry. With numerous bread brands available, students have more options to choose from, give a challenge for bread manufacturers to compete with one another. This study aims to evaluate the factors influencing students' bread selection and determine the most preferred brand among UiTM Perlis students. It considers four criteria which are price, taste, packaging, and brand, while the alternatives bread brands are Gardenia, Massimo, Mighty White, and High Five. A multi criteria decision making method, the Fuzzy Analytical Hierarchy Process (FAHP), is applied to rank the preferred bread among UiTM Perlis students. The FAHP methodology involves data collection, consistency ratio measurement, and FAHP calculations. This approach is able to handle the subjective judgments of consumers. The results indicate that brand is the most influential factor, while the factor of price takes the lowest. Gardenia has become as the most preferred brand, followed by Mighty White, with High Five being the least favoured. This study provides valuable view of the students' bread preferences, helping industry players better understand consumer behaviour in the bread market while also improving their business and marketing strategies.